Analisis Pengaruh Pelayanan dan Standar Operasional prosedur (SOP) terhadap Loyalitas nasabah pada Sebuah Perusahaan - Putra, Aidil; Simorangkir, Niastyna; Manalu, Pius Deski (JOURNAL ECONOMICS AND STRATEGY, 2025)
This study aims to determine how much influence the Service and Standard Operating Procedures (SOP) have on customer loyalty at company. The research methodology used is descriptive quantitative method, the unit of analysis in this study is campany and its observation unit are customers of campany. The population in this study were customers of campany, as many as 35 respondents. The technique of determining the number of samples used in this study amounted to 35 respondents. The research method used is the data collection technique through library research and field research which is carried out systematically based on the research objectives. The analytical method used to solve problems and prove the hypothesis is descriptive analysis, regression analysis. This analysis includes validity and reliability, classical assumption test, multiple regression analysis, hypothesis testing through t and F tests, and the coefficient of determination (R2). From this analysis, it is obtained the regression analysis of Customer Loyalty = 6,182 + 0,082 Service + 0.375 SOP.